(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The use of renewable energy sources on board ships is one solution to reduce pollution from maritime transport. Considering it one of the many solutions for the transition to "zero" emission ships, we studied the possibility of installing a new type of power plant on ships already in operation that uses solar/photovoltaic and wind energy conversion systems. The current electricity production system is transformed into a hybrid system, and by improving the available electrical power management algorithms, clean energy consumption will be prioritized. Monitoring daily electricity consumption and recording values for renewable energy source parameters during ship periods and voyages enabled calculations to determine the potential for electricity production from renewable sources and demonstrated the viability of the chosen solution. The results obtained highlight that installing the ecological marine power plant (ENPP) can achieve significant reductions in fuel consumption for producing electricity on board the ship.